Functionalization of Recycled Diatomite for Green, Stable, and High-performance Phase Change Material (PCM) Composite. (July 2018) - Shih, Yeng-Fong; Wang, Chih-Hung; Tson, Zong-Gi; Zhang, Yu-Cheng; Lian, Hong-Yuan
Abstract: This study reports on the functionalization of recycled diatomite (DT) for preparing green and shape-stabilized phase change material (SSPCM); the DT-based SSPCM can be employed in HDPE composite for high latent heat and good thermal conductivity. After purification, the purified DT (P-DT) adsorbed polyethylene glycol (PEG) by the straight dipping process for producing SSPCM. P-DT showed high surface area of 58 m2g-1 and low organic impurity (<1%); the PEG/P-DT SSPCM exhibited high latent heat of 45 Jg-1 and low leakage (<0.3%). By adding PEG/P-DT SSPCM into the HDPE, the SSPCM/HDPE composite improved both the heat deflection temperature (HDT) and maximum decomposition temperature (Tmax) to 89.18? and 500.2?, respectively. In seeking to enhance tensile strength and thermal conductivity, maleated polyethylene (MAPE) and alumina (Al2O3) were studied in the SSPCM/HDPE composite. In the end, the SSPCM/HDPE composite exhibited great heat resistance, mechanical property and thermal conductivity.